NF-κB/mTOR/MYC Axis Drives PRMT5 Protein Induction After T Cell Activation via Transcriptional and Non-transcriptional Mechanisms - Webb, Lindsay M.; Narvaez Miranda, Janiret; Amici, Stephanie A.; Sengupta, Shouvonik; Nagy, Gregory; Guerau-de-Arellano, Mireia (Frontiers in Immunology, 2019)
Multiple sclerosis is an autoimmune disease of the central nervous system (CNS) mediated by CD4+ T cells and modeled via experimental autoimmune encephalomyelitis (EAE). Inhibition of PRMT5, the major Type II arginine methyltransferase, suppresses pathogenic T cell responses and EAE. PRMT5 is transiently induced in proliferating memory inflammatory Th1 cells and during EAE. However, the mechanisms driving PRMT5 protein induction and repression as T cells expand and return to resting is currently unknown. Here, we used naive mouse and memory mouse and human Th1/Th2 cells as models to identify mechanisms controlling PRMT5 protein expression in initial and recall T cell activation. Initial activation of naive mouse T cells resulted in NF-B-dependent transient Prmt5 transcription and NF-B, mTOR and MYC-dependent PRMT5 protein induction. In murine memory Th cells, transcription and miRNA loss supported PRMT5 induction to a lesser extent than in naive T cells. In contrast, NF-B/MYC/mTOR-dependent non-transcriptional PRMT5 induction played a major role. These results highlight the importance of the NF-B/mTOR/MYC axis in PRMT5-driven pathogenic T cell expansion and may guide targeted therapeutic strategies for MS.